2016
DOI: 10.1093/aob/mcw082
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between soil nutrients and mycorrhizal associations of twoBipinnulaspecies (Orchidaceae) from central Chile

Abstract: The results suggest that soil nutrient availability modulates orchid mycorrhizal associations and provide support for the hypothesis that specialization is favoured by higher soil nutrient availability. Inter-specific differences in mycorrhizal composition can arise due to a geographical pattern of distribution of orchid mycorrhizal fungi, host preferences for fungal partners or differential performance of mycorrhizal fungi under different nutrient availabilities. Further experiments are needed to evaluate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 57 publications
1
30
0
Order By: Relevance
“…In the present study, plants from soils with higher P content had lower levels or even absence of mycorrhizal fungi. However, Mujica et al (2016) found that mycorrhizal associations are favoured by higher soil nutrient availability and suggested that orchid species in nutrient-poor soils may exhibit generalist associations. In our study mycorrhizal association increased in comparatively low P which agrees with the above finding.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, plants from soils with higher P content had lower levels or even absence of mycorrhizal fungi. However, Mujica et al (2016) found that mycorrhizal associations are favoured by higher soil nutrient availability and suggested that orchid species in nutrient-poor soils may exhibit generalist associations. In our study mycorrhizal association increased in comparatively low P which agrees with the above finding.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, this evidence suggests that OMF species differ in ability to support orchids among habitats and climatic conditions (McCormick et al ., ; Kohler et al ., ; Fochi et al ., ; Mujica et al ., ). Genotypic and epigenetic differences among strains of OMFs may also affect their ability to support orchids.…”
Section: Orchid Mycorrhizal Fungus Identity and Orchid Distribution Amentioning
confidence: 97%
“…Similarly, Mujica et al . () found that two species of Bipinnula associated with different OMF taxa and different diversities of OMFs as a function of soil nutrients. Weedy orchids that associated with a wide range of fungi also associated with different fungi among habitats (Bonnardeaux et al ., ).…”
Section: Orchid Mycorrhizal Fungus Identity and Orchid Distribution Amentioning
confidence: 98%
See 1 more Smart Citation
“…In nature, niche partitioning is an important process that allows co-existence of species with similar resource requirements (Schoener, 1974) such as soil fungal communities (Peay et al, 2008). In accordance with the expectation that closely related species have separate niches in at least one dimension, vertical separation has been demonstrated for sister species of soil fungi as a result of competitive avoidance (Mujica et al, 2016). In the current study we use niche separation as a dimension for ecological species recognition.…”
Section: Richness Estimates Based On Clustering At 985% Of Environmementioning
confidence: 88%